Analysis of nursing assessment terminology for neurological conditions and its cross‐mapping with the International Classification of Functioning, Disability and Health (ICF): A multi‐centre cross‐sectional study. Issue 5 (24th March 2021) - Pan, Hongying; Ding, Shanni; Liu, Xiaona; Zou, Zhaojun; Xu, Qunli; Ye, Zhihong
Abstract: Aim: To analyse the application status of nursing assessment terminology for neurological conditions and determine whether the International Classification of Functioning, Disability, and Health (ICF) covers nursing assessment. Design: A multi‐centre cross‐sectional study. Methods: Four researchers extracted all nursing problems from the patients of three different hospitals and formed a pool of nursing terminology from the electronic nursing records, self‐reports, family reports, medical examinations, and clinical records for all patients. The ICF Linking Rules were then used to map the nursing assessment terminology of neurological conditions with the ICF. Results: Though 37.5% of nursing assessment terms were closely related to neurological diseases, this does not appear in the existing electronic nursing assessment records. The unrecorded rate of 9 (16.1%) terms ranged from 40%–50%, while the unrecorded rate of 8 (14.3%) terms was more than 80%. Overall, 96.4% of nursing assessment terms could be described by the corresponding categories of the ICF, with 37 (66.1%) of the "same" concepts, 9 (16.1%) "similar" concepts, 6 (10.7%) "narrower" concepts (the nursing assessment terms were more specific than the ICF categories), and 2 (3.6%) "broader" concepts (the nursing assessment were less specific than the ICF categories).